Survey of power quality in Turkish national transmission network - Kocatepe, Celal; Kekezoglu, Bedri; Bozkurt, Altug; Yumurtaci, Recep; Inan, Aslan; Arikan, Oktay; Baysal, Mustafa; Akkaya, Yener (Tubitak Scientific & Technological Research Council Turkey, 2013)
Harmonic distortion and flicker severity have become the main concerns in power transmission networks. Different types of harmonic and flicker sources exist in power systems, such as arc furnaces and cycloconverters. A power quality problem found in networks can cause additional temperature rise, losses, noise, and irritation in the lighting equipment. The aim of this study is to identify the level of harmonics and flicker in the 380-kV transmission network of Turkey. The measurement and analysis are performed using a specially developed power quality analyzer. The effects of harmonics and flicker on the network are discussed based on real measurement results. Moreover, the measurement results are compared to the current regulations in Turkey.
Keywords: Transmission network; power quality; harmonic; flicker; power quality events; MONITORING-SYSTEM; Computer Science; Engineering